Characteristics of Patients who Survived Less than Three Months or Greater than Two Years after Surgery for Spinal Metastases: Can We Avoid Inappropriate Patient Selection?. Issue 1 (April 2016) - Verlaan, Jorrit-Jan; Choi, D.; Oner, F. C.
Introduction: The survival of patients with metastatic cancer has improved at the cost of increased presentation with metastatic spinal disease. For patients with (impending) pathological spinal fractures and/or spinal cord compression, surgical intervention may relieve pain and improve mobility and quality of life. It is generally accepted that surgery is inappropriate if anticipated survival is less than three months, and survival greater than two years is uncommon. The aim of this international multicenter prospective cohort study was to analyze data from surgical patients who died within three months, or after two years from surgery, to identify any preoperative factors which might be associated particularly with poor survival, to avoid inappropriate selection of patients for surgery in the future. Patients and Methods: A total of 1266 patients were treated surgically for (impending) pathological fractures and/or neurological deficits and were prospectively followed. Data collected included tumor characteristics, preoperative fitness (ASA), neurological status (ASIA), performance status (KPS), and quality of life (EQ-5D). Primary outcomes were survival at three months and two years postsurgery. Univariate and multivariate logistic regression analysis were used to find preoperative factors associated with short- and long term survival. Results: In univariate analysis age, emergency surgery, KPS, EQ-5D, ASA, ASIA, and Tokuhashi/Tomita scores were all significantly associated with short survival. In multivariate analysis, however, only KPS was significantly associated with short survival (OR 1.40; CI 1.18–1.67). Associated with longer survival in univariate analysis were age, number of spinal levels included in the surgery, KPS, EQ-5D, ASIA, and Tokuhashi/Tomita scores. In multivariate analysis, only the number of affected spinal levels included in the surgery was significantly associated with longer survival (OR 1.21; CI 1.03–1.41). Conclusion: Poor performance status at presentation is the strongest indicator of poor survival (less than 3 months), whereas a low disease load with fewer involved spinal levels is strongly associated with longer term survival.